Interferon-Lambda: A Potent Regulator of Intestinal Viral Infections - Lee, Sanghyun; Baldridge, Megan T. (Frontiers in Immunology, 2017)
Interferon-lambda (IFN-λ) is a recently described cytokine found to be of critical importance in innate immune regulation of intestinal viruses. Endogenous IFN-λ has potent antiviral effects and has been shown to control multiple intestinal viruses, and may represent a factor that contributes to human variability in response to infection. Importantly, recombinant IFN-λ has therapeutic potential against enteric viral infections, many of which lack other effective treatments. In this mini-review, we describe recent advances regarding IFN-λ-mediated regulation of enteric viruses with important clinical relevance including rotavirus, reovirus, and norovirus. We also briefly discuss IFN-λ interactions with other cytokines important in the intestine, and how IFN-λ may play a role in regulation of intestinal viruses by the commensal microbiome. Finally, we indicate currently outstanding questions regarding IFN-λ control of enteric infections that remain to be explored to enhance our understanding of this important immune molecule.